2017
DOI: 10.1080/07420528.2017.1411360
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, molecular and hormonal adaptations to early morning versus afternoon resistance training

Abstract: It has been clearly established that maximal force and power is lower in the morning compared to noon or afternoon hours. This morning neuromuscular deficit can be diminished by regularly training in the morning hours. However, there is limited and contradictory information upon hypertrophic adaptations to time-of-day-specific resistance training. Moreover, no cellular or molecular mechanisms related to muscle hypertrophy adaptation have been studied with this respect. Therefore, the present study examined eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…However, this was only partially successful. Whereas the increases in MT (~0.14% increase/day) and fiber CSA (~0.28% increase/ day) of the vastus lateralis muscle were similar to those observed in previous studies (5,18,43), the number of myonuclei remained unaffected by training. A possible explanation for this may be that the increase in fiber hypertrophy was too small (Ͻ20% in CSA and no significant increase in single fiber volume).…”
Section: Discussionsupporting
confidence: 87%
“…However, this was only partially successful. Whereas the increases in MT (~0.14% increase/day) and fiber CSA (~0.28% increase/ day) of the vastus lateralis muscle were similar to those observed in previous studies (5,18,43), the number of myonuclei remained unaffected by training. A possible explanation for this may be that the increase in fiber hypertrophy was too small (Ͻ20% in CSA and no significant increase in single fiber volume).…”
Section: Discussionsupporting
confidence: 87%
“…A critical aspect of training adaptation (particularly for strength-based athletes) and the efficacy of exercise with age is the hypertrophic response within the muscle. While extensive research suggests that athletic performance peaks in the evening, it is unclear whether the muscle-intrinsic hypertrophic response is affected by the time of day at which resistance training occurs [102]. Hypertrophy is correlated with mTOR (mechanistic target of rapamycin) signaling [103], which exhibits circadian regulation in mouse liver [104].…”
Section: Box 3: Clock Control Of Anabolic Responsesmentioning
confidence: 99%
“…The literature on this subject is limited and presents conflicting results. Earlier studies have shown that resistance training in the morning and afternoon periods produce similar gains in muscle strength, volume and cross-sectional area (CSA) after an 10-week (Sedliak et al 2009) or 11-week (Sedliak et al 2018) training period on untrained subjects. However, in another study, greater muscle CSA improvement was observed when RT was conducted in the morning compared to the evening (Küüsmaa et al 2016).…”
Section: Introductionmentioning
confidence: 99%